Transarterial embolization with ONYX for treatment of intracranial non-cavernous dural arteriovenous fistula with or without cortical venous reflux. (10th February 2011) - De Keukeleire, Katrien; Vanlangenhove, Peter; Kalala Okito, Jean-Pierre; Hallaert, Giorgio; Van Roost, Dirk; Defreyne, Luc
Abstract : Background and purpose: To report our experience with transarterial ONYX embolization of intracranial non-cavernous dural arteriovenous fistulas (DAVFs) with or without cortical venous reflux. Materials and methods: Retrospective analysis of transarterial ONYX embolization in 20 patients with 21 DAVFs, presenting with intracranial hemorrhage (n=7), pulsatile bruit (n=7), vertigo (n=3), non-pulsatile bruit (n=1), headache (n=1) and epilepsy (n=1). Risk grading of DAVFs was Borden type I (n=6), type II (n=4) and type III (n=11). Results: 18 of 21 (85.7%) DAVFs were angiographically occluded immediately after embolization, with ONYX embolization only, in either one (n=12) or two sessions (n=2); with a combination of ONYX and glue or transvenous coiling in a single session (n=2) or in two sessions (n=1); or after previous transvenous coiling/glue embolization (n=1). At the 6 (4–14) month control digital subtraction angiography (DSA), available in 14 of 18 occluded DAVFs, one patient showed a small residual fistula (17/21 or 81% occluded). Mid-term DSA was not available because of early death (n=2) or patients were awaiting the examination (n=2). In three cases, treatment was incomplete. Of six Borden type I DAVFs, four were cured and two partially occluded with resolution of symptoms. In two DAVFs, neurosurgical access to the feeding artery allowed distal microcatheterization and successful embolization. Conclusion: Transarterial ONYX embolization offers an effective and safe treatment for all non-cavernous DAVFs, whether with or without cortical venous reflux.